Typologie de L’insertion Professionnelle des Personnes Diplomees de L’Universite - Trottier, Claude; Cloutier, Renee; LaForce, Louise (Canadian Journal of Higher Education, 1994)
The objectives of this paper are a) to delimit the notion of vocational integration, b) to formulate a vocational integration typology for university graduates, taking into account both the «traditional» method of integration (integration at the end of bachelor's degree and rapid stabilization on the labour market), and other methods where integration occurs in phases and stabilization on the labour market follows later, c) to demonstrate the empirical relevance of the typology. The data analysis was based on a data bank on the progression through school and labour market entry of all persons who received undergraduate degrees from Université Laval in 1986. This analysis was not conducted in order to generalize the results for the Quebec population as a whole but rather to demonstrate the typology's relevance and empirical usefulness.